ON THE PROBLEM OF SUBJECTIVITY (AGENCY) OF CONSUMPTION OF EDUCATIONAL SERVICES - Posypanova O. S.; Krasnoshchechenko I.P.; Arpentieva M. R.; Kassymova G. K.; Pogodina I.V.; Bogach M.A.; Varlakova Yu. R. (Scientific Journal of Pedagogy and Economics, 2021)
Many researchers agree that the main activity of the university is the provision of educational services. But they do not give an unambiguous definition in what form the service exists, what is meant by the product or product of the university, as well as how the concepts of "educational service" and "quality of education" are related and also practically do not ask the question of what role the subjectivity of the consumer plays (students, etc.) in the consumption of these services. On the one hand, it is obvious that the problem of consumption of educational services is largely a problem of the quality and price of education: the quality of educational services and prices for educational services. Experts who talk about the development of a person's creative and predictive abilities in relation to the ethical component in the changing educational and social conditions believe that at present, especially, more and more new requirements are imposed on the quality of education. Taking into account the constant variability of the social environment, the very concept of "quality of education" in the future will constantly transform. On the other hand, the problem of formulating the concept of "educational services" has not yet been resolved. In general, an educational service is a complex process aimed at transferring knowledge and skills (competencies) of a general educational, professional nature to the consumer in order to satisfy and develop personal, group and social needs. The quality of educational services changes due to changes in the qualifications of personnel, material and technical base and other elements inherent in the educational process, as well as the quality of students, including their learning ability and other characteristics. The purpose of the study is to analyze the problems of subjectivity in the context of the consumption of educational services.